Resolusi Konflik Ekologis Pada Masyarakat Muslim Rawa Pening Kab. Semarang - Ridwan, Benny (Community Development: Jurnal Pengembangan Masyarakat Islam, 2017)
The condition of Rawa Pening is currently worrying because ecological problems such as sedimentation, proliferation of water hyacinth sporadically, pollution by household waste, hotel, and restaurant, poor water quality, the establishment of cage, and fishing by the use of branjang klambu (nets), electrofishing and poison have led to conflicts. The foregoing is considered social, cultural, and economic resources to be solved and parsed academically. This study aims to clarify the role of the Muslim community of Rawa Pening in overcoming environmental conflict, the factors affecting the role of the community, the importance of awareness and social solidarity of the Muslim community for the preservation of the environment, and the relationship of understanding the teachings of the Muslim community of Rawa Pening to the development of environmental preservation culture. The data collection is done by observation, documentation and interview. The analyzed using the interpretative approach and heuristics. The role of Muslim community in addressing environmental conflict is to make the ban not to use electrofishing, not to do illegal fishing, and not to use poison, all of which abound in village regulations. Besides that, they also clean the swamp, fetch sedekah (alms) as a form of ngabekten (devotion), change the water hyacinth into a blessing, do excavation of the bottom of the swamp as well as maintain and remove Grass Carp fish. The factors that affect the role of the community are the spiritual consciousness, ethics, and social solidarity of the Muslim community.